Academic medical centres in the Netherlands: muddling through or radical change? - Ester M. M. Cardinaal; Martijn J. H. Tjan; Patrick P. T. Jeurissen; Hubert Berden (Frontiers Media S.A., 2024)
IntroductionAcademic medical centres (AMCs) are designed to perform multiple tasks within a single organisation. This institutional complexity gives rise to intricate governance challenges and promotes incrementalism and muddling.MethodIn this study, we hypothesised that radical change could provide a solution to the current incrementalism and we explored the conditions under which such changes could or could not be achieved.ResultsWe conducted unstructured interviews with various high-level stakeholders and identified issues that negatively affected the governance of Dutch AMCs, which include: 1) negative undercurrents and unspoken issues due to conflicts of interests, 2) organisational complexity due to relationships with a university and academic medical specialists, 3) lack of sufficient government direction, 4) competition between AMCs due to perverse systemic incentives, 5) different interests, focus, and organisational culture, 6) concentration of care, which does not always lead to enhanced quality and efficiency as the provision of less complex care is of utmost importance for education and research, 7) the infeasibility of public and regional functions of an AMC, 8) the inefficiency of managing three core tasks within the same organisation and, 9) healthcare market regulation.DiscussionOur hypothesis that radical change offers a solution to the current incrementalism in AMCs could not be adequately explored. Indeed, our exploration of the conditions under which radical change could potentially take place revealed that there are factors currently at play that make a substantive conversation between stakeholders about radical change difficult, if not impossible. The results also show that the government is in a position to take the lead and create conditions that foster mutual trust and common interests among AMCs, as well as between AMCs and other hospitals.